A comprehensive update on antibiotics as an emerging water pollutant and their removal using nano-structured photocatalysts. Issue 2 (April 2021) - Roy, Namrata; Alex, Sruthi Ann; Chandrasekaran, N; Mukherjee, Amitava; Kannabiran, Krishnan
Graphical abstract: Highlights: Extensive antibiotic utilization promotes antibiotic resistance in microorganism. Organizational level of intervention has controlled the global antibiotic pollution rate. Metal and metal oxide nanoparticle degrade antibiotics via photocatalytic mechanism. Free Radical generation by the novel nanoparticles promotes antibiotic degradation. Lower Bandgap energies of the nanoparticles improve the degradation efficiency. Abstract: Diverse antibiotic drugs have been used for the treatment of bacterial infections; however, their overuse, improper handling, and limitations in treatment facilities can result in their accumulation and biotransformation in the water systems. These bio-accumulated antibiotics can lead to more detrimental effects due to the emergence of multi-resistant bacterial genes at the micro-level, which in turn enhance the chances of bacterial survival. The current review discusses the prevalence of this contaminant in India and different countries around the globe. Since prevention of antibiotic release is the most effective strategy for controlling water pollution, the importance of several governing bodies and their guidelines for antibiotic use and release have been discussed. As a solution to the increasing threat of antibiotics in treated wastewater and natural waters, various treatment strategies have been explored, of which photocatalytic degradation is one of the significant treatment options. In particular, the review focuses on the multiple approaches of photocatalytic degradation in a stand-alone system and in combination with other techniques and nanomaterials. Different photo-active materials, reactor systems, oxide molecular release, kinetic mechanisms, influence of different parameters and characterizations involved have been discussed in detail in order to understand the optimum conditions for photocatalytic degradation of antibiotics.